Progress on new drug treatments for hepatic echinococcosis - Li, Yunzhang; Xie, Nana; Chai, Jinping; Jing, Qindong; Liu, Linxun; A, Jide; Pan, Hongshuai (Frontiers in Pharmacology, 2026)
Echinococcosis: is a zoonotic parasitic disease caused by infection with the larvae of Echinococcus tapeworms. At present, the standardized treatment regimen for this disease consists of radical lesion resection combined with albendazole. For patients who are inoperable or experience postoperative recurrence, the treatment with anti-echinococcosis drugs is particularly crucial. To date, albendazole remains the primary drug clinically used for anti-echinococcosis treatment. However, it has inherent drawbacks such as low bioavailability, poor solubility, long treatment course, and multiple adverse reactions, which reduce the medication adherence of patients with echinococcosis and compromise the clinical therapeutic efficacy. In recent years, with the in-depth development of research in molecular biology, pharmacology, and natural medicines, significant progress has also been made in the field of anti-echinococcosis drugs. This article systematically reviews the research progress in the development of new anti-echinococcosis drugs from four aspects: structural modification and new formulations of benzimidazole drugs, targeted drug therapy, combined medication strategies, and exploration of natural medicines and active components of traditional Chinese medicines.